Ṣu`ūbāt Ta`allum Mahārah al-Kitābah Wa Ṭuruq `Ilājihā Fī Qism Ta`līm al-Lughah al-`Arabiyyah Bi IAIN Takengon - Maulidati Maulidati (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
Maharah kitabah is the fourth maharah after maharah istimak, kalam and qiraah. Kitabah is very important to be studied by every student, especially Arabic language students, to support the perfection of learning Arabic. However, along with the learning process, many students complain about the difficulties they face in studying. This study aims to see what are the obstacles faced by students in learning Maharah Kitabah by reviewing two aspects, namely the aspect of Kitabah Wal Imla' and Ta'bir Kitabi. The method used in this study is a qualitative method, data collection techniques are carried out by observation, interviews, and the results of student Imla' and Insha' exercises. As for the research results obtained, researchers found that the difficulties faced by students in learning Maharah Kitabah were very diverse. First: in terms of Kitabah and Imla', students are weak and slow in writing, they don't master the Nahwu Sharaf rules, they don't understand the rules of Arabic writing, the student's ability to listen to material dictated by the teacher is weak. Second: in terms of the interpretation of the book. Students are not able to compose sentences and paragraphs in perfect form, Tadakhul Lughawi, at least memorized vocabulary, limited ideas, and opinions, afraid of being wrong, lack of interest in material Ta'bir Kitabi, lazy to look for references or read, not too good at the material so they are confused about what to write.